Scanning aldoxime dehydratase sequence space and characterization of a new aldoxime dehydratase from Fusarium vanettenii - Křístková, Barbora; Rädisch, Robert; Kulik, Natalia; Horvat, Melissa; Rucká, Lenka; Grulich, Michal; Rudroff, Florian; Kádek, Alan; Pátek, Miroslav; Winkler, Margit; Martínková, Ludmila (Enzyme and microbial technology, 2023)
The aim of this work was to map the sequence space of aldoxime dehydratases (Oxds) as enzymes with great potential for nitrile synthesis. Microbes contain an abundance of putative Oxds but fewer than ten Oxds were characterized in total and only two in fungi. In this work, we prepared and characterized a new Oxd (protein gb|EEU37245.1 named OxdFv) from Fusarium vanettenii 77-13-4. OxdFv is distant from the characterized Oxds with a maximum of 36% identity. Moreover, the canonical Oxd catalytic triad RSH is replaced by R141-E187-E303 in OxdFv. R141A and E187A mutants did not show significant activities, but mutant E303A showed a comparable activity as the wild-type enzyme. According to native mass spectrometry, OxdFv contained almost 1 mol of heme per 1 mol of protein, and was composed of approximately 88% monomer (41.8 kDa) and 12% dimer. A major advantage of this enzyme is its considerable activity under aerobic conditions (25.0 ± 4.3 U/mg for E,Z-phenylacetaldoxime at pH 9.0 and 55 °C). Addition of sodium dithionite (reducing agent) and Fe2+ was required for this activity. OxdFv favored (aryl)aliphatic aldoximes over aromatic aldoximes. Substrate docking in the homology model of OxdFv showed a similar substrate specificity. We conclude that OxdFv is the first characterized Oxd of the REE type.
Keywords: Catalysis; Catalytic triad; Hydro-Lyases; Homology modeling; oximy; dehydratasy; Oximes; Aldoxime dehydratase; Nitrile synthesis; Fusarium; katalýza; Fusarium vanettenii; Substrate docking